1979
DOI: 10.1037/h0081571
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sex role deviance in disturbed male adolescents on the perception of psychopathology.

Abstract: The purpose of this study was to investigate the effect of sex role deviance on the perception of psychopathology, and to correlate the size of this effect with measures of sex role ideology and gender stereotyping. The study employed a person perception rating task in which subjects evaluated written case histories of sex role deviant and sex role congruent male adolescents with emotional and behavioral problems. Male adolescents were judged to be more disturbed if their hobbies, career aspirations, and inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1980
1980
1984
1984

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…being better adjusted (Costrich, Feinstein, Kidder, Maracek & Pascale, 1975;Seyfried & Hendrick, 1973;Tilby & Kalin, 1979), are evaluated as more likable (Seyfried & Hendrick, 1973;Shaffer & Wegley, 1974;Spence, Helmreich & Stapp, 1975), and have their task performance rated more favorably (Cohen & Bunker, 1975;Deaux & Taynor, 1973;Mischel, 1974). Such findings are consistent with predictions from role theory, that out-of-role behavior fails to meet role standards, and therefore should receive negative sanctions.…”
supporting
confidence: 80%
“…being better adjusted (Costrich, Feinstein, Kidder, Maracek & Pascale, 1975;Seyfried & Hendrick, 1973;Tilby & Kalin, 1979), are evaluated as more likable (Seyfried & Hendrick, 1973;Shaffer & Wegley, 1974;Spence, Helmreich & Stapp, 1975), and have their task performance rated more favorably (Cohen & Bunker, 1975;Deaux & Taynor, 1973;Mischel, 1974). Such findings are consistent with predictions from role theory, that out-of-role behavior fails to meet role standards, and therefore should receive negative sanctions.…”
supporting
confidence: 80%
“…Several studies from the context of sex roles have confirmed this prediction. Persons having sex role appropriate as opposed to inappropriate behaviours or interests are judged as being better adjusted (Tilby & Kalin, 1979 and are rated to be more likeable (Spence, Helmreich & Stapp, 1975). Stoppard & Kalin (1978) have shown an overlap between gender stereotypes and sex roles.…”
Section: N -I I Assertive Figurementioning
confidence: 99%
“…Feminist (and other) psychologists in Canada, as elsewhere, have been attracted by the androgyny notion (Schneider & Coutts, 1979;Tilby & Kalin, 1979;Woolsey, 1977). Supporting evidence for the validity of the androgyny construct was obtained by Vancouver researchers Wiggins and Holzmuller (1978).…”
Section: Researchmentioning
confidence: 95%
“…Pyke (1974b) has delineated some of the problems experienced by the feminist which may lead her to seek counselling. And, an interesting study by Tilby and Kalin (1979) revealed that mildly disturbed male adolescents presented as sex-role deviant are perceived as less mature, more disturbed, more difficult to treat and having poorer prognosis than similarly disturbed sex-role congruent adolescents. In this same vein, a survey of Colwill and Roos (1978) debunked the stereotype that female medical students in Canada are sex-role deviant and disinterested in sex.…”
Section: Sex Roles and Psychological Weil-beingmentioning
confidence: 99%